Hubungan Self-Management dengan Prokrastinasi Akademik Pada Siswa Kelas X di SMA Negeri 4 OKU - Rahmayati, Selly; Puriani, Risma Anita (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2025)
Self-management is a crucial factor that contributes to the reduction of academic procrastination. This study aims to investigate the relationship between self-management and academic procrastination among 10th-grade students at SMA Negeri 4 OKU. Employing a quantitative correlational design, the study sampled 156 students selected through simple random sampling using Slovin’s formula from a total population of 254 students. The data were collected using questionnaires comprising scales for both self-management and academic procrastination. Analysis was conducted using the Pearson Product Moment correlation method. Findings revealed that the levels of self-management and academic procrastination among the students were 42% and 40%, respectively, both falling within the moderate category. The correlation coefficient was calculated at -0.772 with a significance level of 0.000 (p 0.05), demonstrating a statistically significant negative correlation between self-management and academic procrastination. This indicates that an improvement in students’ self-management skills is associated with a decrease in their academic procrastination tendencies.